Классическая механика как основа современных методов моделирования свойств материалов: пример вибрационной релаксации - Вихренко, В. С. (БНТУ, 2004)
It is emphasized that classical mechanics is a film basis for computer modeling a variety of phenomena on macro-, meso- and microscopic levels. Vibrational relaxation is considered as an example.